2009
DOI: 10.2522/ptj.20080139
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effects of High-Intensity Laser Therapy Versus Ultrasound Therapy in the Treatment of People With Subacromial Impingement Syndrome: A Randomized Clinical Trial

Abstract: Participants diagnosed with SAIS showed greater reduction in pain and improvement in articular movement functionality and muscle strength of the affected shoulder after 10 treatment sessions of HILT than did participants receiving US therapy over a period of 2 consecutive weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
162
1
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(183 citation statements)
references
References 50 publications
6
162
1
14
Order By: Relevance
“…These finding are similar to the study done by Santamato et al (2009) [8] who observed a significantly greater reduction pain in the LASER treated group compared to the Ultrasound treated group having patients suffering from Sub-acromial impingement syndrome after the treatment for 10 treatment sessions over period of two consecutive weeks.…”
Section: Resultssupporting
confidence: 81%
“…These finding are similar to the study done by Santamato et al (2009) [8] who observed a significantly greater reduction pain in the LASER treated group compared to the Ultrasound treated group having patients suffering from Sub-acromial impingement syndrome after the treatment for 10 treatment sessions over period of two consecutive weeks.…”
Section: Resultssupporting
confidence: 81%
“…Santamato et al evaluated the short-term effectiveness of HILT versus ultrasound therapy in the treatment of subacromial impingement syndrome (SAIS). Participants in the HILT group showed significantly greater decrease in pain than participants in the US therapy group [10]. Zati et al evaluated the efficacy of HILT, compared with accepted therapies such as TENS and NSAIDs.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on the use of HILT have concerned its impact on the treatment of shoulder joint pain in the impingement syndrome. Ten sessions of therapeutic radiation at a wavelength of 1,064 nm at 2,050 J and 6 W reduced joint pain, increased the range of motion, and improved the muscle strength of the shoulder (Santamato et al 2009). An analysis of the impact of HILT on women with fibromyalgia showed that exposure of each tender point on the body to laser light of the two wavelengths of 810 nm and 980 nm at 600 J effectively reduced the pain felt by patients, positively affected the mobility of the upper part of the body, and reduced the overall physical discomfort (Panton et al 2013).…”
Section: Human Medicinementioning
confidence: 99%